2019
DOI: 10.32098/mltj.01.2014.18
|View full text |Cite
|
Sign up to set email alerts
|

No difference at two years between all inside transtibial technique and traditional transtibial technique in anterior cruciate ligament reconstruction

Abstract: Background: one of the most recent technique is the "all inside" anterior cruciate ligament (ACL) reconstruction. One of the main characteristic of this procedure is the sparing of the tibial cortex. Furthermore, the all-inside technique requires only one tendon harvested. Purpose: the present study describes two year clinical outcomes of the all-inside method for ACL reconstruction, and compares them with clinical results of a group of patients treated with the traditional transtibial single-bundle ACL recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 20 publications
2
35
0
5
Order By: Relevance
“…However, the data could not be pooled, given it was assessed in different ways and at different times. The individual studies reported comparable postoperative pain and analgesic consumption for both the all-inside and full tibial tunnel groups at all follow-up times [12,13,15]. Return to sports was investigated by two studies [8,11]; however, the data were recorded in a different time frame.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the data could not be pooled, given it was assessed in different ways and at different times. The individual studies reported comparable postoperative pain and analgesic consumption for both the all-inside and full tibial tunnel groups at all follow-up times [12,13,15]. Return to sports was investigated by two studies [8,11]; however, the data were recorded in a different time frame.…”
Section: Discussionmentioning
confidence: 99%
“…The selected studies reported that the study period included the surgeon's learning curve on the newly developed all-inside technique. The unfamiliarity with the surgical instrument and fixation device might be the cause of all these complications [3,8,9,12,13]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the data could not be pooled, given it was assessed in different ways and at different times. The individual studies reported comparable postoperative pain and analgesic consumption for both the allinside and full tibial tunnel groups at all follow-up times (12,14,19). Return to sports was investigated by two studies (15,16); however, the data were recorded in a different time frame.…”
Section: Discussionmentioning
confidence: 99%
“…In autologous graft selection, six studies (3,14,(16)(17)(18)(19) used quadrupled semitendinosus tendon (ST4) in the all-inside group and double gracilis and semitendinosus tendon (DGST) in the full tibial tunnel group; one study did not clearly mention the autologous tendon graft donor site (15). All the studies mentioned the suspensory cortical button graft fixation device was used on both the femoral and tibial side in the all-inside group of patients.…”
Section: Graft Harvest and Fixation Devicementioning
confidence: 99%
“…However, the data could not be pooled, given it was assessed in different ways and at different times. The individual studies reported comparable postoperative pain and analgesic consumption for both the all-inside and full tibial tunnel groups at all follow-up times (12,14,19). Return to sports was investigated by two studies (15,16); however, the data were recorded in a different time frame.…”
Section: Discussionmentioning
confidence: 99%